Some Notes about Architecture, Urbanism and Economy - José Manuel Pagés Madrigal (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
The economy can be considered as the transversal component of human activities over territories. This fact can be observed from a diachronic perspective: the way how architectural typologies arose through history. But the relations between Economy and Architecture are not only established by the small scales but the larger ones. Cities and territories evolved from compact forms till spread ones in a parallel way to the arousal of the shopping areas. Urban sprawl could never be understood without these new typologies. The paper is based on the keynote speech was held in the International seminar “Economy today” last September 2017 in Andrigrad (Bosnia and Herzegovina). It is divided into two blocks: the first one relates to a general review of the historical reflections of this relation with a special mention to the consequences of an economic crisis either in the landscape or urban scales. The second part, partially included in the conclusions, reflects on the necessary changes in the university curriculums for better visualization of this relation. It would imply new attitudes able to explain most of the architectural processes as the formal result of a larger interaction.